Rancang Bangun Smart Irrigation Tanaman Cabai Berbasis IoT - Dudi Ali; Imam Suharjo (Universitas Mercu Buana Yogyakarta, 2022)
The development of the current era is increasing, people expect a technology that can facilitate their activities or work. One of them is in agriculture such as irrigation systems. The irrigation system is one of the factors that determine the success of agriculture because without sufficient water, most of the crops that become agricultural commodities will not thrive. However, the current irrigation system still uses the manual method which still has some drawbacks, for example, the use of too much water. As in chili plants, the amount of water to be given to chili plants cannot be determined. The easiest way to check is to make sure the soil is moist on the chili plant. For this reason, in this final project, a tool is made that can check soil moisture and plant waters automatically. This tool was built to make it easier for farmers to check soil moisture and provide water to plants, especially chili plants. This tool uses a soil moisture sensor or soil moisture sensor which is used to check soil moisture and send data to Arduino to turn on the water pump. In making this final project, a system is designed that is able to take advantage of the development of science and technology to facilitate the work of farmers. In this technology, a system was developed to open and close irrigation canals using a microcontroller that can be connected to the android application.